Evaluación de la ganancia de peso en conejos reproductores en el ceypsa - Ligña Quinaucho, Carola Paulina (2016)
The following research project was conducted in the experimental and produce center of Salache. It was directed toward the increase in weight of stud rabbits, and there is a data base (weight), starting from both phenotypical parameters and breed features of each animal with a suitable management, identification, and grouping of specimens on study thanks to installations, resources and materials which were provided by the institution so as to improve the reproductive rate in such species. 32 adult specimens on reproductive stage were used. They were divided up into three different categories, from which the first category was 4 Californian female rabbits. The second category was 4 Neozeland male rabbits and finally the third category was settled on 24 Neozeland female rabbits. Red earrings numbered from 1 to 100 were used and assigned to each on the central part of the right ear.